ON-DEMAND RELAPAROTOMY AND PROGRAMMED SANITIZATION IN THE TREATMENT OF WIDESPREAD PERITONITIS - Djuraeva Zilola Aramovna; Tokhirov Sheroz Mardonkulovich; Mustafakulov Ishnazar Boynazarovich (Research Focus International Scientific Journal, 2026)
The choice of tactics for repeat surgical interventions for disseminated peritonitis remains a subject of debate. The aim of this study was to compare the effectiveness of on-demand relaparotomy and programmed debridement relaparotomies in patients with disseminated peritonitis. Clinical treatment outcomes, complication rates, and mortality were analyzed. It was found that an individualized approach using on-demand relaparotomy with dynamic clinical and laboratory monitoring reduces surgical trauma and the incidence of postoperative complications without increasing mortality.